Monitoring Transformations of Catalytic Active States in Photocathodes Based on MoSx Layers on CuInS2 Using In Operando Raman Spectroscopy - Chae, Sang Youn; Yoon, Noyoung; Joo, Oh shim; Park, Eun Duck (Angewandte Chemie - International Edition, 2023)
The electrochemical activation of CuInS2/MoSx for photoelectrochemical (PEC) H2 production was revealed for the first time through in operando Raman spectroscopy. During the activation process, the initial metallic MoSx phase was transformed to semiconducting MoSx, which facilitates charge carrier transfer between CuInS2 and MoSx. Ex situ X-ray photoelectron spectroscopy and Raman spectroscopy suggest the existence of MoO3 after the activation process. However, apart from contradicting these results, in operando Raman spectroscopy revealed some of the intermediate steps of the activation process.
Keywords: Activation process; Active state; Electrochemical activation; H 2 evolution; H 2 production; In operando raman spectroscopy; Metallics; Mosx; Operando; Photoelectrochemicals; CuInS2; H2 Evolution; in Operando Raman Spectroscopy; Mosx; Photoelectrochemical Cell